Deciphering the Anode-Enhanced Azo Dye Degradation in Anaerobic Baffled Reactors Integrating With Microbial Fuel Cells - Yang, Yonggang; Luo, Ou; Kong, Guannan; Wang, Bin; Li, Xiaojing; Li, Enze; Li, Jianjun; Liu, Feifei; Xu, Meiying (Frontiers in Microbiology, 2018)
Microbial anode respiration in microbial fuel cells (MFCs) can enhance the degradations of many electron acceptor-type contaminants such as azo dyes which are presumed to be competitive to each other. To understand the mechanisms of those counter-intuitive processes, this study integrated MFCs into anaerobic baffled reactor (ABR), termed MFC-ABR, for the degradation of azo dye acid orange-7 (AO-7). Compare with ABR, MFC-ABR enhanced the reduction of AO-7, especially at high AO-7 concentration (800 mg/L). Moreover, acute toxicity test suggested a higher detoxication efficiency in MFC-ABR. Higher microbial viability, dehydrogenase activity and larger sludge granule size were also observed in MFC-ABR. MFC-ABR significantly enriched and reshaped the microbial communities relative to ABR. Bacteria with respiratory versatility, Pseudomonas, Geobacter and Shewanella, were significantly enriched. Functional prediction showed that six metabolism functions (manganese-, iron-, fumarate- and nitrate-respiration, oil bioremediation and chemoheterotrophy) were significantly stimulated while methanogenesis, sulfate_respiration, hydrogen_oxidation were suppressed in MFC-ABR relative to ABR. The results provided important information for understanding the interactions among different microbial respirations in practical environments.